Valuing visitor services and access to protected areas: The case of Nyungwe National Park in Rwanda. (August 2017) - Lal, Pankaj; Wolde, Bernabas; Masozera, Michel; Burli, Pralhad; Alavalapati, Janaki; Ranjan, Aditi; Montambault, Jensen; Banerjee, Onil; Ochuodho, Thomas; Mugabo, Rodrigue
Abstract: Policymakers and recreation site managers use changes in fee structure, either introducing park entrance fees or increasing existing ones, to generate revenues, improve services, and reduce damages associated with over-use. Increase in park usage fee, however, can make the park inaccessible to certain segments of tourists. Understanding park users' response to changes in fees and its implication on park use equity is, thus, important to achieving a park's full potential in a socially and environmentally responsible way. This information is crucial especially for developing countries, where the issue has received relatively less attention and national park systems are chronically underfunded. This paper contributes to the literature on park access fees by: empirically assessing park use equity between and among international and national tourists visiting Nyungwe National Park, Rwanda, and; developing an approach for determining predictors and mean willingness to pay values for park entrance. Results of our survey-based approach show a positive willingness to pay values for park entrance and fee increases. Our results also show that it is possible to raise revenue without exacerbating existing park use differences. Highlights: International tourists have higher park use tendency compared to national tourists. Differences in income and education level explain differences in park use among national tourists. Tourists, both national and international, are willing to pay park entrance fees and higher recreational service fees. Differential pricing and socioeconomic differences among tourists help explain willingness to pay. Revenue analyses show net gain without necessarily increasing park use differences.